Digitalization of accounting - Kupenova, Zh.K.; Baymukhanova, S.B.; Zhunisova, G.E.; Zhunissova , Zh.T. (BUKETOV BUSINESS REVIEW, 2023)
Object: To identify problems that arise in the process of digitalization of accounting, consider ways to implement digital transformation, suggest ways to improve the quality and efficiency of the accounting apparatus of an enterprise. Methods: To justify the need to introduce digitalization into the accounting industry, identify the main digital technologies, identify the problems and benefits of transformation, an analysis of existing digital technologies was carried out. The study proposes ways to address pressing issues such as digital transformation planning and the shortage of skilled workers in this area. Findings: The novelty of this article lies in the prerequisites for the introduction of digital technologies in the accounting department of an enterprise. As a result of the study, the need for the accumulation of competencies in the field of digital technologies and the introduction of digitalization in accounting was identified. Conclusions: The main conclusion of the article is the need to digitize the accounting aspect in order to generate reliable data on the financial condition of the company.